Brassinolideand castasterone-induced modifications of growth processes and biomass accumulation in in vitro culture of Phalaenopsis × hybridum Blume protocorms - Charnysh, Maryia A.; Przhevalskaya, Darya A.; Horski, Ilya A.; Kolbanov, Dmitrii V.; Zhabinskii, Vladimir N.; Khripach, Vladimir A.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2019)
Brassinosteroids is a class of plant steroid hormones, which mainly targets growth, development and stress responses in higher plants. Nevertheless, their effects on the growth of orchid plants and orchid in vitro cultures, which are used in biotechnology, have not been studied in details. The objective of this work was to characterize effects of major brassinosteroids, such as brassinolide and castasterone, on the growth and development of Phalaenopsis × hybridum Blume protocorms in vitro. The obtained data show that both brassinolide and castasterone cause significant increase of the physical size and weight of Phalaenopsis protocorms. As low as 0.1 nmol ⋅ L–1 of brassinolide and castasterone in the medium induced statistically significant stimulation of growth processes. 2–3-fold increase in biomass and length was inducedby addition of 0.1–1.0 µmol ⋅ L–1 of brassinolide and castasterone. Treatment by brassinosteroids increased the length of roots but did not change their quantity and developmental characteristics. Thus, results of this study clearly show that brassinosteroids are promising agents for regulation of orchid growth, which can act in extremely low concentrations and cause the pronounced stimulatory effects on growth but not on the development. Treatment by brassinosteroids as well as studying their effects on the physiological characteristics of ornamental orchids in vitro culture can potentially have an impact on the fundamental knowledge in the field of plant physiology and on the development of new biotechnologies.
Keywords: Phalaenopsis × hybridum Blume; brassinosteroids; seeds propagation; protocorms; in vitro culture